Dystocia due to fetaI anasarca in a buffalo - SINGH, BHOOPENDRA; SINGH, S V; SINGH, K P; SINGH, B K; SINGH, H N (The Indian Journal of Animal Reproduction, 2007)
Fetal anasarca occurs due to autosomal recessive gene and can cause severe dystocia especially whendead fetus becomes emphysematous. Dystocia due to fetal anasarca in a buffalo and its relief by forced traction is described.
Keywords: Dystocia; Buffalo; Fetal anasarca